2018
DOI: 10.20344/amp.10442
|View full text |Cite
|
Sign up to set email alerts
|

Resposta à Carta ao Editor: “Prevalência de Literacia em Saúde Inadequada em Portugal Medida com o Newest Vital Sign”

Abstract: suggest that the Portuguese version of the Newest Vital Sign (NVS) should not be used to assess older adults in clinical practice because of a floor effect. We disagree. A floor effect is a problem when the performance on the test does not reflect the true performance in the domain being assessed.1 This is not the case here. We are not classifying older people incorrectly by using the NVS. Another study using a different health literacy instrument, one that asks people questions about their perceived difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
1
0
0
1
Order By: Relevance
“…When comparing our results with previous studies [31][32][33][34][35] that evaluated health literacy in adolescents and adults, we observed that our sample presented a higher prevalence of inadequate health literacy. We found that 73.3% of our sample had inadequate health literacy, including 95.1% of adolescents and 53.3% of adults.…”
Section: Discussionsupporting
confidence: 63%
“…When comparing our results with previous studies [31][32][33][34][35] that evaluated health literacy in adolescents and adults, we observed that our sample presented a higher prevalence of inadequate health literacy. We found that 73.3% of our sample had inadequate health literacy, including 95.1% of adolescents and 53.3% of adults.…”
Section: Discussionsupporting
confidence: 63%
“…Desta forma, devem adotar medidas universais, tais como: uso linguagem simples sem terminologias específicas e técnicas; concentração de informação estritamente necessária; repetição de informações chave; uso de ilustrações, vídeos e/ou demonstrações; concessão de documentação fácil de ler e que complemente as instruções orais; assegurar que o paciente compreendeu a informação transmitida. (PAIVA et al, 2017).…”
Section: O Acesso Da Pessoa Com Deficiência Visual à Saúde: Desafios E Potenciais Facilitadoresunclassified